2011
DOI: 10.1007/s11356-011-0666-2
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium, kinetic and thermodynamic studies on the biosorption of reactive acid dye on Enteromorpha flexuosa and Gracilaria corticata

Abstract: Both the algal biomasses had heterogeneous surfaces and followed pseudo second-order chemical kinetics. Thermodynamic parameters proved that the biosorption by both the biomasses were spontaneous, feasible and endothermic processes. Desorption studies proved the worth of the algal biomasses as biosorbents in industrial level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…2), indicating that at pH < 2.80, the surface of the peat would be positively charged and at pH > 2.80, it would be negatively charged. The pH pzc of peat experimentally determined in this research is similar to that of algal biomass, 35 which also has a high organic matter content. Above the pH pzc , the pH of the peat suspension if greater than the initial pH, suggesting that there is a tendency for the peat surface to become negatively charged with exposed hydroxyl groups, promoting the adsorption of cationic dyes, such as BG.…”
Section: Characterization and Surface Chemistry Of Peatsupporting
confidence: 64%
“…2), indicating that at pH < 2.80, the surface of the peat would be positively charged and at pH > 2.80, it would be negatively charged. The pH pzc of peat experimentally determined in this research is similar to that of algal biomass, 35 which also has a high organic matter content. Above the pH pzc , the pH of the peat suspension if greater than the initial pH, suggesting that there is a tendency for the peat surface to become negatively charged with exposed hydroxyl groups, promoting the adsorption of cationic dyes, such as BG.…”
Section: Characterization and Surface Chemistry Of Peatsupporting
confidence: 64%
“…Therefore, laccaic acids could interact with the cell wall material of algae in an analogous way to the non‐covalent interactions with chitosan. Other Gracilaria species have shown potential for the biosorption of dyes from aqueous solution, including the acid dye Benewol Red by G. fisheri , CI Acid Black 1 by G. persica biomass , and the removal of reactive acid dye, methylene blue, and crystal violet by G. corticata . In the case of G. corticata biomass, it was shown that the biosorption mechanism of crystal violet from aqueous solution occurred by electrostatic interactions between the negatively charged seaweed surface and positively charged crystal violet cations .…”
Section: Introductionmentioning
confidence: 99%